MPO-ANCA-positive crescentic glomerulonephritis superimposed on a mesangial proliferative glomerulonephritis in a patient with mixed cryoglobulinemia due to hepatitis C infection: a case report - Rodrigues,Luís (2014)
Renal involvement of antineutrophil cytoplasmic antibodies (ANCA) associated vasculitis typically occurs in the form of a pauci-immune crescentic glomerulonephritis. The finding of some immune complex deposits in these glomerulonephritis is not unusual, but the cases with greater than mild deposition suggest the presence of a second and immune complex related glomerular disease. The significance of the immune complex deposits and their role in ANCA associated vasculitis is still a topic of debate, but higher levels of proteinuria and worse prognosis with respect to renal function have been described in these patients. We report a case of a patient with a known mesangial proliferative glomerulonephritis related to a mixed cryoglobulinemia secondary to a chronic hepatitis C infection that later developed a rapidly progressive glomerulonephritis due to a superimposed anti-myeloperoxidase ANCA positive glomerulonephritis.